Persistent debt and business cycles in an economy with production heterogeneity - Aubhik Khan; Soyoung Lee (Bank of Canada, 2023)
We study an economy with a time-varying distribution of production to examine the role of debt in amplifying and propagating recessions. In our model, entrepreneurs use risky, long-term debt to finance capital. Liquid assets serve as collateral and transaction costs make debt illiquid. Debt payments increase the volatility of earnings relative to output, deterring entrepreneurs with insufficient collateral from financing efficient levels of capital. This results in a misallocation of resources. In a large recession, productive entrepreneurs with high levels of debt deleverage, amplifying the downturn. The model economy exhibits asymmetries over the business cycle. Recessions involve a rapid deterioration of economic activity, while expansions are more gradual. When a recession coincides with a rise in leverage resulting from a fall in assets, fewer producers operate at efficient levels. When the aggregate business leverage is ten percentage points above average, the half-life of the recovery doubles.
Keywords: E23; E30; E32; 330; Business fluctuations and cycles; Firm dynamics; Productivity